The Digital Asset Contribution Toward the MSME’s Performance in Bekasi during COVID-19 Pandemic Era - Apriani, Siti Zulaikha Dwi; Kaban, Reny Fitriana; Pasaribu, Popy Novita (Ekonomi Bisnis, 2021)
This study aims to determine the contribution of digital assets such as social media, websites, and online marketplace to the performance of MSMEs of Bekasi City in the era of the Covid-19 pandemic. The population in this study is business owners/managers with a maximum annual turnover of 10 billion rupiah and assets of 50 billion rupiahs. This research uses a quantitative approach with the primary data source in the form of a questionnaire. Using Partial Least Square as a data processing and analysis technique, the results show that the social media, website, and online marketplace have been proven to have a contribution to the performance of MSMEs in Bekasi City, especially during the Covid-19 pandemic.